Dhikr (Recitation) and Relaxation Improve Stress Perception and Reduce Blood Cortisol Level in Type 2 Diabetes Mellitus Patients with OAD - Amir, Faisal; Mastutik, Gondo; Hasinuddin, M; Putra, Suhartono Taat (Folia Medica Indonesiana, 2018)
Recitation and relaxation are translated as stimuli that can turn disstraints into uneven conditions (balanced conditions). The purpose of this study was to explain the effect of remembrance and relaxation on improving stress perception and decreasing blood cortisol levels in patients with type 2 diabetes mellitus with Anti Diabetes Medication (OAD). This type of research is quasi-experimental with the non randomized control group pretest posttest design. The population in this study were all type 2 diabetes mellitus patients at the Internal Poly department of Syarifah Ambami Hospital Rato Ebu Bangkalan. The study sample was divided into 2 groups, namely control and intervention, each of which was 14 respondents. First, respondents were asked to fill out an informed consent form, identity, fill in the Depression Anciety Stress Scale 42 questionnaire (DASS 42) and examine cortisol levels as pre-treatment data. Then for 6 weeks the intervention group was given remembrance and relaxation treatment, while the control group was only given health education. After 6 weeks the second group respondents were asked to fill in DASS 42 and examined cortisol levels as data after treatment. Difference data before and after the treatment was tested for normality using Shapiro-Wilk and obtained normal data distribution so that the different tests used independent T test with a = 0.05. Recitation and relaxation can significantly improve stress perception with p value (0.001) <0.05 and reduce cortisol levels with p value (0.024) <0.05. Recitation and relaxation improve stress perception so that the hypothalamic pituitary adrenal (HPA) axis produces a balanced level of the hormone cortisol. Cortisol in a balanced level will improve various metabolic processes.